Isu Kesehatan Mental Pasangan Suami Istri yang Belum Memiliki Keturunan di Usia Pernikahan di Atas 5 Tahun - Handayani, Eka Sri (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
One of the social expectations and demands that couples must face is that they must have children, at least in the first year after marriage. This is based on the statement of a woman who has never been pregnant and has not had children after several years of marriage. These demands greatly affect the status of women in society. This suggests that if a woman is unable to bear children, her social status is considered lower than women who have children. This shows the magnitude of social demands that must be faced by women who do not have children. Marital unhappiness can also be seen in further inability to adapt, for example the development of psychosomatic illnesses, depression, anxiety, infidelity, alcoholism, cruel treatment of children. The data collection method in this research uses interview, observation and documentation methods. After obtaining the data, it is analyzed descriptively qualitatively, because descriptive research is very simple, namely just asking or collecting information and reporting the results. Descriptive research is research into the status, attitudes, opinions of groups of individuals, sets of conditions and procedures, a system of thoughts or events in order to create a systematic and analytical description.